The Effect of System Quality, Social Influence, and Price Value on Intention to Use Digital Banking - Sabita, Farah; Riandi, Muhammad Hafiz (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The development of digital technology has encouraged transformation in banking industry and given birth to the era of digital banking. However, the transition to digital platforms is still hampered by the doubts and reluctance of some customers. The objective of this research is to identify the effects of system quality, social influence, and price value on the intention to use digital banks. The population of this quantitative explanatory research is Generation Z and Millennials in Malang city; 130 of them were selected as the respondents via non-probability sampling method, or more specifically purposive sampling technique. The data has been assessed for their validity, reliability, and goodness of fit and was examined using descriptive analysis, multiple linear regression, and coefficient of determination. The hypothesis testing was performed using t-test. This study finds that system quality, social influence, and price value have significantly positive influence the intention to use digital banks. The implication of this research is the appropriate use of strategies that will address system quality, social influence, and price value in order to increase the intention to use digital banks.